2020
DOI: 10.1186/s12986-020-00443-1
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose itself plays a critical role on lipid metabolism: Trehalose increases jejunum cytoplasmic lipid droplets which negatively correlated with mesenteric adipocyte size in both HFD-fed trehalase KO and WT mice

Abstract: Background: Trehalose is a functional disaccharide that has anti-metabolic activities such as suppression of adipocyte hypertrophy in mice and alleviation of impaired glucose tolerance in humans. Trehalase hydrolyzes trehalose in the small intestine into two glucose molecules. In this study, we investigated whether trehalose can suppress adipocyte hypertrophy in mice in the presence or absence of trehalase. Methods: Trehalase knockout (KO) mice and wild-type (WT) mice were fed a high fat diet (HFD) and adminis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…12 Trehalose participated in the process of lipid metabolism that could suppress adipocyte hypertrophy. 13 The negative effect on adipogenesis might be a positive effect on osteogenesis. Additionally, a previous study also demonstrated that Trehalose could improve bone mass in cirrhosis rats by increasing the formation of autophagosome, which indicated autophagy might play an important role in the treatment of osteoporosis by Trehalose.…”
Section: Introductionmentioning
confidence: 99%
“…12 Trehalose participated in the process of lipid metabolism that could suppress adipocyte hypertrophy. 13 The negative effect on adipogenesis might be a positive effect on osteogenesis. Additionally, a previous study also demonstrated that Trehalose could improve bone mass in cirrhosis rats by increasing the formation of autophagosome, which indicated autophagy might play an important role in the treatment of osteoporosis by Trehalose.…”
Section: Introductionmentioning
confidence: 99%
“…Its "career" started as a cell stabilizer in the dry state [12], and emerged so rapidly that a myth grew up about trehalose as a universal protectant and chemical chaperone [13]. Indeed, this disaccharide is important for widespread industrial and medical applications [13][14][15][16][17]. In yeast, trehalose is synthesized in a two-step process in which glucose-6-phosphate and UDP-glucose are converted to trehalose-6-phosphate by trehalose-6-phosphate synthase (Tps), then trehalose-6-phosphate is converted to trehalose by trehalose-6-phosphate phosphatase.…”
Section: Introductionmentioning
confidence: 99%
“…Trehalose and LT reduced fructose‐induced hepatic steatosis and induced hepatocyte fasting response signals, PGC1α, TFEB, and FGF21. Extrahepatic cardiometabolic effects of these compounds are broad, including peripheral insulin sensitization [118], activating peripheral thermogenesis, reduced adipocyte hypertrophy [119,120], in addition to reduced atherosclerotic plaque lesion area [27,121] and pathological cardiac remodeling in response to injury [122,123], that mimicked ketogenic dietary effects on heart failure [37]. Treating liver‐specific GLUT8‐deficient mice with oral trehalose did not increase the efficacy of trehalose on diet‐induced hepatic steatosis, which implies some mechanistic overlap between GLUT8 deletion and trehalose action [9].…”
Section: Restricting Hepatocyte Carbohydrate Entry Mimics the Broader...mentioning
confidence: 99%